The Freezing of Some Nutrients Using Plasma - Maryam G. jasim (Genius Journals, 2023)
Certain foodborne germs produce resistant spores and poisons, reducing the efficacy of most green technology. Formerly, plasma's primary usage was in surface disinfection; today, it is also widely employed in the food processing business. They are removing hazardous bacteria from food and food items like fruits, vegetables, dairy, and meat using plasma, cutting-edge green technology, or environmentally friendly techniques. Inactivating spores and deactivating enzymes and toxins, respectively, are areas where the modern technology of cold plasma has proven to be vastly superior. Cold plasma consists of free electrons, ions, reactive atomic and molecular species, and ultraviolet (UV) radiation created when a gas is ionized nonthermal. However, the specific mechanism by which cold plasma is effective has remained unknown. Optimal optimization and widespread use of cruel plasma treatment in food processing require understanding these mechanisms and the likely elements that can restrict or boost their effectiveness and effects. For example, there is no thermal damage or limited output variation when using cold plasma to modify the surface of solid or liquid foods (because of the wide variety of gas, power, plasma type, and other input parameters).
Keywords: Plasma at room temperature; microbiological spores; food safety